2012
DOI: 10.1016/j.gaitpost.2011.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Rapid force generation is impaired in cerebral palsy and is related to decreased muscle size and functional mobility

Abstract: Limb movements involving contraction times of 50–200ms occur in many everyday activities, such as gait, which is faster than the time required to generate maximal force. Therefore, the ability to rapidly produce force may be even more important for the performance of functional activities. In this study rate of force development (RFD) and impulse of the knee extensors were examined in 12 ambulatory children with cerebral palsy (CP) (Age:11.9 ± 2.9 yrs) and 11 with typical development (TD) (Age: 11.3 ± 3.0 yrs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 33 publications
5
106
0
2
Order By: Relevance
“…We used two different measures that relate to muscle weakness in the subjects. MVC is a measure of the maximal strength that the subjects may generate when given ample time, whereas RFD is a measure of the ability of the subjects to generate force as quickly as possible within the early part of a muscle contraction (Aagaard et al, 2002, Suetta et al, 2004, Moreau et al, 2011. RFD of either dorsiflexors or plantar flexors correlated better than MVC for all kinematic measures of gait function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used two different measures that relate to muscle weakness in the subjects. MVC is a measure of the maximal strength that the subjects may generate when given ample time, whereas RFD is a measure of the ability of the subjects to generate force as quickly as possible within the early part of a muscle contraction (Aagaard et al, 2002, Suetta et al, 2004, Moreau et al, 2011. RFD of either dorsiflexors or plantar flexors correlated better than MVC for all kinematic measures of gait function.…”
Section: Discussionmentioning
confidence: 99%
“…For all RFD intervals, the average muscle strength of the CP-group was much lower than the controls. For the 0-200 ms time-interval (RFD200 df ), which is often regarded as the maximum time available for many everyday movements to occur (Suetta et al, 2004, Moreau et al, 2011, the adults with CP produced only 21% of the torque produced by the controls (28.3 ± 6.6 Nm/s vs. 137.5 ± 11.2 Nm/s; p < 0.001). For the MVC df , the adults with CP produced 42% of the torque produced by the controls (15.8 ± 3.8 Nm vs. 37.7 ± 2.4 Nm; p < 0.001).…”
Section: Passive and Reflex-mediated Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they have greater efficiency and are used for activities that need strength [2,33]. A review of the literature has shown that few studies [1,8,17,20,29] go beyond a description of muscle length changing during a crouching gait, and no references were found in sport application and above all in knee up move analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Power training which combines both force and velocity components may be beneficial as it targets both strength development (through increase of sarcomeres in parallel) and velocity development (through increase of sarcomeres in series) which has been greatly associated to functional activities [9]. Moreau et al (2012) observed that the combination of RFD and MVC predicted 77% of variance in overall gait function, which might be due to the fact that each variable accounts for different functions during gait, power and force respectively. Furthermore, muscles with different functions (power and force) should also be combined as together they better predict performance on functional scales than alone [8].…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%